Well‐formed cerebellum and brainstem‐like structures in a mature ovarian teratoma: Neuropathological observations. Issue 2 (2nd January 2017) - Shintaku, Masayuki; Sakuma, Toshiko; Ohbayashi, Chiho; Maruo, Motoyoshi
Abstract : In the surgical case of a mature cystic teratoma of the ovary that arose in a 16‐year‐old girl, a large amount of well‐differentiated and highly organized cerebellar tissue was found. Three layers of the cerebellar cortex were well formed, and synaptophysin‐positive "glomeruli" were found in the granule cell layer. Some Purkinje cells exhibited focal expansion and a dysmorphic appearance of the dendrites. Adjacent to the cerebellar tissue, a large space lined by the ependymal layer and a club‐shaped CNS tissue mass resembling the brainstem were found, and structures reminiscent of the midbrain tectum and pontine nuclei were distinguished within this mass. The CNS tissue was surrounded by the leptomeninges and a skull‐like, bony shell. Structures consistent with the supra‐tentorial CNS tissue were not found. This case represents an example of infra‐tentorial CNS tissue that was well‐differentiated and organized to an exceptionally high degree in an ovarian mature teratoma. Various degenerative changes have been documented in CNS tissue in ovarian teratomas, but the dendritic abnormalities of Purkinje cells seen in the present case are novel findings.